2006
DOI: 10.1095/biolreprod.105.049486
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of Cyclin D2 by the PKA Pathway and Inducible cAMP Early Repressor in Granulosa Cells1

Abstract: Cyclin D2 (Ccnd2) is an essential gene for folliculogenesis, as null mutation in mice impairs granulosa cell proliferation in response to FSH. Ccnd2 mRNA is induced during the estrus cycle by FSH and is rapidly inhibited by LH. Yet, the responsive elements and transcription factors accounting for the gene expression of cyclin D2 in the ovary have not been fully characterized. Using primary cultures of rat granulosa cells and immortalized mouse granulosa cells, we demonstrate a mechanism for the regulation of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Our findings suggest a differentiated response of ␤-cells to extracellular growth factors with cyclin A2 being responsive to the cAMP-PKA-CREB-CBP pathway, whereas the D-type cyclins possibly respond to growth factor stimuli other than cAMP or PI 3-kinase (36). Previous reports have suggested that cyclins D1 and D2 respond to the cAMP pathway in in vitro cell systems (37)(38)(39). We do not find any evidence for exendin-4 or CREB-CBPmediated elevation in D-type cyclins.…”
Section: Exendin-4 Stimulation Of Cyclin A2mentioning
confidence: 61%
“…Our findings suggest a differentiated response of ␤-cells to extracellular growth factors with cyclin A2 being responsive to the cAMP-PKA-CREB-CBP pathway, whereas the D-type cyclins possibly respond to growth factor stimuli other than cAMP or PI 3-kinase (36). Previous reports have suggested that cyclins D1 and D2 respond to the cAMP pathway in in vitro cell systems (37)(38)(39). We do not find any evidence for exendin-4 or CREB-CBPmediated elevation in D-type cyclins.…”
Section: Exendin-4 Stimulation Of Cyclin A2mentioning
confidence: 61%
“…We (above) and others (24,29) have found that cAMP signaling has a potent effect on CCND2 transcription, which is mediated by a conserved CRE site located immediately 5′ to the transcriptional origin (29). CREM repressors regulate CCND2 by binding this CRE (24).…”
Section: Discussionmentioning
confidence: 79%
“…We (above) and others (24,29) have found that cAMP signaling has a potent effect on CCND2 transcription, which is mediated by a conserved CRE site located immediately 5′ to the transcriptional origin (29). CREM repressors regulate CCND2 by binding this CRE (24). Repressor isoforms of CREM share the DNA binding and dimerization domains of CREM activators but lack kinase and trans-activation domains and therefore act as potent dominant negative transcription inhibitors (30)(31)(32).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The question of whether loss of G s ␣/cAMP signaling directly leads to cyclin D2 deficiency in ␤ cells requires further study, although recent studies in both lymphocytes and ovarian granulosa cells demonstrated that cAMP induces the Ccnd2 gene promoter via binding of PKA-phosphorylated CREB to a CREB binding site (31,32). Cyclin D2 and its associated cyclin-dependent kinase cdk4 have both been shown to be critical regulators of ␤ cell proliferation and ␤ cell mass (3)(4)(5)(6)(7)33).…”
Section: Discussionmentioning
confidence: 99%